Quantifying soil surface erosion - Philippe, Pierre; Benahmed, Nadia (Comptes Rendus. Physique)
This review first introduces the general context of soil erosion, an omnipresent natural process involving a wide variety of spatial and temporal scales. While this loss of solid matter induced by all kinds of fluid flows on the surface of soils is often a source of beauty in the landscapes that surround us, it also constitutes a major risk and poses growing threats in the context of global change as loss of agricultural soil fertility, decline in coastal ecosystems or increase in safety standards for flood protection structures. It is therefore essential to be able to predict future soil removal rates at multiple scales, in order to anticipate or mitigate their impacts. This requires experimental quantification of soil’s vulnerability to erosion. In order to describe this type of measurement in deeper detail, we restricted the scope of our review to situations of concentrated surface erosion of homogeneous soils, on moderate spatial and temporal scales, as typically studied in the fields of civil or environmental engineering. Measuring erosion itself is challenging, both in terms of determining the rate of mass removal from a surface, and in terms of selecting and quantifying a relevant hydrodynamic quantity to reflect the strength exerted by the flow. A conceptual framework is then required to correctly define soil’s erodibility, which is defined as an intrinsic property of the material through an empirical erosion law. In the most commonly accepted approach, this erodibility combines two distinct parameters: an erosion initiation threshold, generally chosen as a critical shear stress, and an erosion kinetic coefficient. The various types of erodimeters found in literature are then presented and compared, with a specific and more complete description of the three main devices used in geomechanics (EFA, HET and JET). Finally, before concluding and suggesting some perspectives on the topic, we outline the various advantages and applications of the erodibility values derived from experimental tests, while showing the limitations of the approach and the questions raised by them.